2022
DOI: 10.2337/dc21-2643
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate Tolerance Threshold for Unannounced Snacks in Children and Adolescents With Type 1 Diabetes Using an Advanced Hybrid Closed-Loop System

Abstract: OBJECTIVE To find a carbohydrate (CHO) tolerance threshold for unannounced snacks to avoid the 2 h increase in glycemia (difference between pre- and postmeal blood glucose [ΔBG]) ≥50 mg/dL in advanced hybrid closed-loop (a-HCL) users. RESEARCH DESIGN AND METHODS Fourteen children and adolescents with type 1 diabetes (7 females; mean age [± SD] 14.5 ± 3.6 years), users of the Medtronic MiniMed 780G, participated in the study. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 16 publications
2
8
0
Order By: Relevance
“…As shown by Tornese G. et al., autocorrections allow a more liberal approach to dietary aspects of the therapy. The authors revealed that in case of not very exact carbohydrate counts or a missed meal bolus, the AHCL system helped by delivering an autocorrection dose without the patient’s intervention ( 6 ). Similar outcomes presented a study comparing glycemic control for announced and unannounced meal challenges.…”
Section: Discussionmentioning
confidence: 99%
“…As shown by Tornese G. et al., autocorrections allow a more liberal approach to dietary aspects of the therapy. The authors revealed that in case of not very exact carbohydrate counts or a missed meal bolus, the AHCL system helped by delivering an autocorrection dose without the patient’s intervention ( 6 ). Similar outcomes presented a study comparing glycemic control for announced and unannounced meal challenges.…”
Section: Discussionmentioning
confidence: 99%
“…One other meal announcement method has been described for the MiniMed 780G system so far. Unannounced snacks of up to 20 g of carbohydrates can avoid a difference in blood glucose of ≥50 mg/dL in pediatric MiniMed 780G users, and unannounced meals of up to 30 g of carbohydrates are safe ( 15 ). However, the MiniMed 780G system is not designed as a full closed loop system; thus, meal announcement is preferred.…”
Section: Discussionmentioning
confidence: 99%
“…Petrovski et al have shown that a simplified meal announcement with a preset of different fixedcarbohydrate amounts could be used, with 67% of patients in the fix group reaching the target TIR, even with a 6.8% TIR difference in favor of the precise CHO count [15]. Bolus omission and bolus delay are very common, especially among adolescents with T1D, and even though Tornese et al observed that unannounced CHO snack of <20 g of CHO resulted in a tolerable glucose excursion in children and adolescents treated by the Medtronic MiniMed TM 780G [16], it is of utmost importance to ensure patients and their families receive retraining in CHO counting periodically, as well as verifying that meals are announced, and if the insulin/CHO settings are still reliable or if it is the algorithm that does the job. Bolus omission seems an issue that does not concern the study cohort, and the number of meals increased over time.…”
Section: Discussionmentioning
confidence: 99%